Generation of a homogenous glow discharge in air at atmospheric pressure - Buntat, Zolkafle; Harry, J. E.; Smith, I. R. (Faculty of Electrical Engineering, 2007)

(untitled)
A glow discharge has been experimentally investigated in air at atmospheric pressure using two different electrode configurations of a perforated aluminium sheet and stainless steel wire mesh. The observations of the Lissajous figure of voltage-electric charges is used as a method of distinguishing between the glow discharge produced by perforated aluminium sheet and stainless steel wire mesh. The perforated material shows a better glow discharge stabilization than that of stainless steel wire mesh.